Northward migration of Afro-Siberian Knots Calidris canutus canutus : high variability in Red Knot numbers visiting staging sites on the French Atlantic coast, 1979–2009 - Jutta Leyrer; P Bocher; F Robin; P Delaporte; C Goulvent; E Joyeux; F Meunier; T Piersma (2009)
The Afro–Siberian Red Knot subspecies, Calidris canutus canutus, winters mainly on Banc d’Arguin, Mauritania, West Africa. An International Wader Study Group project carried out in 1979 suggested that during northward migration Red Knots cover their migration between the wintering grounds and the Siberian breeding grounds in two long-distance non-stop flights, stopping only in the Wadden Sea in Schleswig-Holstein, Germany. Each year Red Knots also visit staging sites along the French Atlantic coast in addition to the German Wadden Sea. Ever since 1979, the French staging sites have been counted on a regular basis and here we present the count data from these 30 years. In some years more than 20% of the population used the French Atlantic coast as a staging site, but numbers are highly variable from one year to the next. We suggest that high numbers in France might occur when birds have to stop short of the Wadden Sea because of head-winds and/or a lack of tail-winds en route from West Africa.